1991
DOI: 10.1080/00288233.1991.10417688
|View full text |Cite
|
Sign up to set email alerts
|

Effect of meadow spittlebug and Australian crop mirid on white clover seed production in small cages

Abstract: The effects of feeding by the Australian crop mirid (Sidnia kinbergi (StM» and the meadow spittlebug (Philaenus spumarius L.) on white clover (Trifolium repensL.) seedproduction weredetermined by comparing seedyieldcomponents fromuninfested plant clones with those from clones infested with varyingnumbersof the insects.Feedingby thelowest numberofAustralian cropmirid(oneperplant) caused a 50% reduction in the numbers of flower heads produced by the plants, an 18% reduction in the numberof buds producedon each f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 8 publications
1
12
0
Order By: Relevance
“…Loss is based on $4 kg" 1 dressed seed. yields indicate that the bumble bees used for pollination in the cages were efficient, and support the observations made by Pearson (1991). Infestations of PM significantly reduced all components of white clover seed yield (Tables 1 and 2).…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…Loss is based on $4 kg" 1 dressed seed. yields indicate that the bumble bees used for pollination in the cages were efficient, and support the observations made by Pearson (1991). Infestations of PM significantly reduced all components of white clover seed yield (Tables 1 and 2).…”
Section: Discussionsupporting
confidence: 72%
“…The intensities used were recalculated to densities in Table 2 to give an indication of seed yield losses incurred, which could then be used as the basis for developing economic thresholds for PM density in white clover crops. Pearson (1991) released different ACM numbers per white clover clonal plant, but concluded that the same experiment should be conducted within a crop to evaluate the influence of mirids feeding on other plant variables, as described in this experiment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations